Nutrient flows from harvested banana pseudostems - Wortmann, Charles S.; Karamura, E.B.; Gold, C. (1994)
Management of harvested (senescent) banana pseudostems has implications for efficiency of nutrient use for sole cropped as well as intercropped bananas. Two studies were conducted on aspects of nutrient flows from senescent pseudostems. Sixty one and 55% of the initial N and P, respectively, in standing senescent pseudostems were determined to be translocated to attached growing pseudostems at six weeks after harvest. Lesser proportions of the initial K, S, Fe, Zn, Cu and B were translocated; translocation of Ca, Mg and Mn was negligible. Over 50% and 70% of the initial N, K and Mg were released from the mulch of cut and shredded pseudostems by six and nine weeks after harvest, respectively. Other nutrients were released more slowly from the mulch.